Roads to regionalism genesis, design, and effects of regional organizations - Borzel, Tanja A. (International political economy of new regionalisms series, 2012)
Takes a comparative approach across space and time to regional organizations in North and South America, Africa, the Middle East, and Asia. This book describes and explains the genesis and growth of regional organizations. It considers the impact of regional organizations on their member states.